Investigating Inclusion of Safety Metrics for Safe Route Determination on Pedestrian Map - ONG, WEI HAN (Universiti Teknologi Petronas, 2011)
To develop the safest route algorithm, it is important to research on the appropriate safety metrics that will be used to develop the safest route algorithm. Based on the researches conducted, factors such as route visibility, amount of people in the area, area near entertainment district and route condition are important in affecting_ safety of an area. This project focuses on how to include those factors in developing the safest route algorithm for the system and at the same time allow the ease of update/modification of the algorithm. The safest route algorithm developed for the system is tested to prove that the proposed metrics are reliable.